The Appearance of Mother Banana Tree - Pedroni, Maria Angélica (Revista do Colóquio, 2022)
This visual essay shows part of the proposals that make up “Paths of the Earth: Memories of Materiality” (2022), which I presented as my final project for the Visual Arts course at the Federal University of Espírito Santo. These proposals mainly involved ceramics, engraving, and performance. “Mãe Bananeira” is an action that I carried out in the second half of 2022 and was photographed by Matheus Bonela.